Cartographic Skills in Geography Textbooks: A Comparative Analysis of Instructional Materials for Mainstream and Minority Primary Schools in Greece - Giakoup, Sinan (European Journal of Geography, 2026)
The educational rights of the Muslim minority of Thrace, the only officially recognised minority in Greece, are safeguarded by Article 41 of the Treaty of Lausanne (1923). Within this framework, minority education has developed into a distinct subsystem of the Greek educational landscape, historically shaped by the dynamics of Greek–Turkish relations. Since the late 1990s, state policy has prioritised the qualitative improvement of educational provision, leading to targeted initiatives, such as the creation of new textbooks for minority classrooms. The present study investigates, within the field of geography education, the extent to which these textbooks cultivate cartographic skills through the use of maps, comparing the specialised minority school textbooks with those employed in mainstream public education. Situated within the field of geography education and textbook research, the study applies content analysis to the full corpus of maps contained in both textbook categories, classifying them according to a tripartite typology and the type of learning task involved. The results of the analysis demonstrate that minority school textbooks display notable deficiencies relative to their general education counterparts, particularly regarding the systematic integration of map-based learning activities. These findings suggest that the limited presence and pedagogical use of maps in minority school textbooks may contribute to the reproduction of educational inequalities, underscoring the need for policy measures to strengthen spatial and cartographic literacy in minority education. Highlights: Comparative analysis of maps in mainstream and minority school textbooks Minority textbooks include 55.9% fewer maps than general education textbooks Contextual map use predominates in minority textbooks (44.6% of cases)